2011
DOI: 10.1007/s13197-011-0356-6
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of polyphenol oxidase from watermelon juice by high pressure carbon dioxide treatment

Abstract: The inactivation of polyphenol oxidase from watermelon juice with high pressure carbon dioxide (HPCD) treatment was investigated. The maximum reduction of polyphenol oxidase (PPO) activity inactivated by HPCD treatment was 95.8% at 30 MPa and 50°C for 30 min, which was far higher than 50.9% of control treatment at 50°C for 30 min. The inactivation of PPO was adequately described by a two-fraction model, which indicated that a labile and stable fraction might present in PPO from watermelon juice. The kinetic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…The results have been shown in Table 1, the R 2 and v 2 values were found to be in the range of 0.93-0.97 and 0.002-0.01, respectively, which indicate a good fit. Liu et al (2013) reported the D 50 of 12.7 min whereas in present study the D 90 was found 1.92 and 0.63 min for PPO in water melon juice by HW and OH treatment respectively, Chutintrasri and Noomhorm (2005) studied the PPO in pine apple puree and found a D 90 of 11.4 min, such difference could be attributed due to the variation in the product and properties of the product. Hence the present study found that 90% of the PPO could be inactivated by OH treatment in a very short time as compared to the HW treatment.…”
Section: Kinetic Analysiscontrasting
confidence: 50%
“…The results have been shown in Table 1, the R 2 and v 2 values were found to be in the range of 0.93-0.97 and 0.002-0.01, respectively, which indicate a good fit. Liu et al (2013) reported the D 50 of 12.7 min whereas in present study the D 90 was found 1.92 and 0.63 min for PPO in water melon juice by HW and OH treatment respectively, Chutintrasri and Noomhorm (2005) studied the PPO in pine apple puree and found a D 90 of 11.4 min, such difference could be attributed due to the variation in the product and properties of the product. Hence the present study found that 90% of the PPO could be inactivated by OH treatment in a very short time as compared to the HW treatment.…”
Section: Kinetic Analysiscontrasting
confidence: 50%
“…On increasing the EFS, the effect of the EFS proceeded in opposing directions for both the fractions such that the labile fraction was easily disrupted while the stable fraction regained its stability; such observations are yet to be reported for OH treatment. However, Liu et al () reported an increase in the susceptibility of the stable fraction of PPO in water melon juice at high pressures. The possibility of the same phenomenon in sugarcane juice during OH processing was possible.…”
Section: Resultsmentioning
confidence: 99%
“…Limited reports are available on the inactivation kinetics of enzymes by OH. However, a few studies have reported first‐order inactivation kinetics of PPO in apples (Castro, Macedo, Teixeira, & Vicente, ) and a biphasic order of urease inactivation in soymilk (Liu, Hu, Zhao, & Zhang, ). As per the reported literature, PPO inactivation generally followed the first‐order kinetics during application of various technologies like pulsed electric field (medium: buffered solution) and supercritical carbon dioxide in apple juice (Gui et al, ; Zhong et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations